SWFs and their role in the face of Oil shocks - Abadulmahdi Raheem Hamza; Basima N Muhsen; Abbas Jalil Hassan (Iraqi Journal for Administrative Sciences, 2024)
The study aims to analyze and study sovereign funds, which have become one of the most important economic phenomena in the level of international relations, especially with regard to countries whose economies are rentier, including Saudi Arabia, and then contribute to the diversification of these economies by investing in bonds and shares or even participate in the establishment of projects Various investments inside and outside the Kingdom of Saudi Arabia. It also has easy access by the state compared to the foreign exchange reserves of central banks.